2008
DOI: 10.1007/s10461-008-9440-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Anal Intercourse Vary by Partner Type Among Substance-Using Women: Baseline Data from the UNITY Study

Abstract: Data are limited about anal intercourse among women at risk of HIV infection. HIV-negative non-injection drug using women at sexual risk (N = 404) were recruited. At baseline, 41.7% reported anal intercourse in the prior 3 months; of these, 88.2% reported unprotected anal intercourse (UAI). Factors associated with UAI varied by partner type: UAI with a steady partner was associated with younger age, depressive symptoms, and experience of battering; UAI with casual partners was associated with younger age, coca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…In contrast to the original findings of Pulerwitz et al (2000), several studies found no association between RC and condom use frequency (Campbell et al, 2009; Panchanadeswaran et al, 2010; Tietelman et al, 2008). In a study of primarily White women, Knudsen et al (2008) found that higher RC scores were associated with less frequent unprotected anal intercourse, whereas Koblin et al (2010) found no evidence of a significant association between RC and unprotected anal sex in a study of predominantly African American women.…”
Section: Resultsmentioning
confidence: 91%
“…In contrast to the original findings of Pulerwitz et al (2000), several studies found no association between RC and condom use frequency (Campbell et al, 2009; Panchanadeswaran et al, 2010; Tietelman et al, 2008). In a study of primarily White women, Knudsen et al (2008) found that higher RC scores were associated with less frequent unprotected anal intercourse, whereas Koblin et al (2010) found no evidence of a significant association between RC and unprotected anal sex in a study of predominantly African American women.…”
Section: Resultsmentioning
confidence: 91%
“…reported that 72% of women had ever engaged in HAI, with 23% reporting regular HAI [14]. Another study reported that 20% of American women were at high risk of HIV, reporting having had HAI with a variety of partners, including paying clients [17]. A study among Puerto Rican college students in the US found that 44% of males and 32% of females practiced anal sex [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is a behavior that is practiced by 16-35% of teenage couples (Carter et al, 2010;Hensel, Fortenberry, & Orr, 2010;Koblin et al, 2009;Roye, Krauss, & Silverman, 2010). Although homosexuality and bisexuality among women has not received much attention from HIV researchers, there is some evidence that having both male and female sexual partners may be associated with HIV-risk for women.…”
mentioning
confidence: 99%